If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(6+-2n)=-8n-24
We move all terms to the left:
-4(6+-2n)-(-8n-24)=0
We add all the numbers together, and all the variables
-4(-2n)-(-8n-24)=0
We multiply parentheses
8n-(-8n-24)=0
We get rid of parentheses
8n+8n+24=0
We add all the numbers together, and all the variables
16n+24=0
We move all terms containing n to the left, all other terms to the right
16n=-24
n=-24/16
n=-1+1/2
| 2/3=(x+15)/33 | | 0=10(2)+(-3x)+(-4)+2(-2)+2(1) | | 9−4h=3−4h | | -2(-8v+2)-3v=7(v-1)-5 | | 3x/4=28 | | 7(6+d)=49 | | 0=10+5x+2 | | X^2-2x=x+28 | | 2n-35=77-6 | | 0=10(2)=(-3x)+2(-1) | | X/60-x/40=15 | | 3x^2+1/3x=38/3 | | (X-4)(x+4)=x^2-16 | | 9x+18=-10x-14 | | 10=4-(-3k) | | X/40-x/60=15 | | 3(x-2)=188 | | 3x-17=x+4 | | 5(x-7)=5x-7 | | 2^5(10x-5)=18 | | -(n+2)=-14-7n | | 5=x/3=2 | | -6=y/5-1 | | (7x3)-6+1+5=21 | | 1=x/4-3 | | 4x+34=4x-86 | | 3x^2+1x=38 | | 2(b+6)=5+4b-8 | | 8x+8=8x-2 | | 6x-2x+5=4x+8 | | 0.85(x+10)=+0.10(x-5) | | 3x=15=6 |